2021
DOI: 10.3390/pathogens10060763
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Long COVID Prevalence and Its Relationship to Epstein-Barr Virus Reactivation

Abstract: Coronavirus disease 2019 (COVID-19) patients sometimes experience long-term symptoms following resolution of acute disease, including fatigue, brain fog, and rashes. Collectively these have become known as long COVID. Our aim was to first determine long COVID prevalence in 185 randomly surveyed COVID-19 patients and, subsequently, to determine if there was an association between occurrence of long COVID symptoms and reactivation of Epstein–Barr virus (EBV) in 68 COVID-19 patients recruited from those surveyed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
234
2
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(279 citation statements)
references
References 50 publications
(67 reference statements)
8
234
2
10
Order By: Relevance
“…Organ damage caused by an excessive inflammatory response activated by the virus, persistent reservoirs of SARS-CoV-2 in certain tissues that could trigger post-infection morbidity, re-activation of pathogens due to immune dysregulation, host microbiome alterations, clotting/coagulation issues and autoimmunity due to molecular mimicry between SARS-CoV-2 and self-proteins have been hypothesized to play a role [ 10 ]. Furthermore, it has also been suggested that Long COVID symptoms may not be a direct result of the SARS-CoV-2 infection but may be the consequence of COVID-19 inflammation-induced Epstein Bar virus reactivation [ 11 ]. The search for fine molecular mechanisms underlying Long COVID is also underway.…”
Section: Long Covid Etiologymentioning
confidence: 99%
“…Organ damage caused by an excessive inflammatory response activated by the virus, persistent reservoirs of SARS-CoV-2 in certain tissues that could trigger post-infection morbidity, re-activation of pathogens due to immune dysregulation, host microbiome alterations, clotting/coagulation issues and autoimmunity due to molecular mimicry between SARS-CoV-2 and self-proteins have been hypothesized to play a role [ 10 ]. Furthermore, it has also been suggested that Long COVID symptoms may not be a direct result of the SARS-CoV-2 infection but may be the consequence of COVID-19 inflammation-induced Epstein Bar virus reactivation [ 11 ]. The search for fine molecular mechanisms underlying Long COVID is also underway.…”
Section: Long Covid Etiologymentioning
confidence: 99%
“…Other virus reactivations reported after SARS-Cov-2 vaccination including Epstein-Barr virus and we noted a personal case of reactivation of herpes uveitis [ 8 ]. It is not our competence to formulate hypotheses on the mechanisms of reactivation.…”
Section: Discussionmentioning
confidence: 83%
“…This group had tested positive for COVID at least 90 days prior to the study; in a group of participants who tested positive 21–90 days prior to the study, six of nine patients with long COVID symptoms tested positive for EBV reactivation, while only one of eleven did in the control group. While the EBV antibody EBV EA-D IgG was correlated with experiencing long COVID symptoms, neither EBV VCA IgG antibody nor EBNA-1 IgG antibody demonstrated the same association [ 164 ].…”
Section: Factors Involved In Ebv Reactivationmentioning
confidence: 99%